Effect of Intracerebroventricular Administration of Apelin-13 on the Hypothalamus-Pituitary-Thyroid Axis and Peripheral Uncoupling Proteins - Erden, Yavuz; Tekin, Suat; Tekin, Cigdem; Ozyalin, Fatma; Yilmaz, Umit; Onalan, Ebru Etem; Sandal, Suleyman (Springer, 2018)
Apelin, a ligand for G protein-coupled APJ receptor, is a peptide hormone. Although apelin and APJ receptors are determined in hypothalamus and thyroid gland its role in the hypothalamus-pituitary-thyroid (HPT) axis and mechanism of action on energy metabolism is not clear. This suggests that apelin may play a role in the HPT axis and energy metabolism. This study was designed to determine possible effects of centrally administered apelin-13 on the HPT axis and energy metabolism. A total of 40 adult male Sprague Dawley rats were divided into four groups (n=10 each group). Intact rats served as control group while the sham group received vehicle of apelin. Apelin-13 was injected intracerebroventricularly at the doses of 1 and 10nmol, for 7 days in the rats in the experimental group. At the end of the experimental protocol, animals were decapitated and brain, blood, white and brown adipose tissues samples were collected. There was no significant difference between the groups in terms of hypothalamic TRH mRNA levels. Serum TSH levels were significantly higher in all groups compared to the control group (p<0.05). Serum fT3 and fT4 levels were significantly lower in apelin-13 administered groups (p<0.05). Moreover, apelin-13 administered groups had lower levels of UCP1 mRNA in white and brown adipose tissues. UCP3 mRNA expression in muscle tissue was also lower in apelin-13 treated groups (p<0.05). These results indicates that apelin-13 exhibits a decreasing effect on energy consumption through a mechanism involving the peripheral rather than central arms of the HPT axis.
Keywords: Apelin-13; Hypothalamus-pituitary-thyroid axis; Uncoupling protein; Energy metabolism; Thyroid hormones